Lipoprotein(a) and Risk of Myocardial Infarction and Death in Chronic Kidney Disease: Findings From the CRIC Study (Chronic Renal Insufficiency Cohort). Issue 10 (October 2017) - Bajaj, Archna; Damrauer, Scott M.; Anderson, Amanda H.; Xie, Dawei; Budoff, Matthew J.; Go, Alan S.; He, Jiang; Lash, James P.; Ojo, Akinlolu; Post, Wendy S.; Rahman, Mahboob; Reilly, Muredach P.; et al.
Abstract : Objective—: To investigate the effect of LPA gene variants and renal function on lipoprotein(a) [Lp(a)] levels in people with chronic kidney disease and determine the association between elevated Lp(a) and myocardial infarction and death in this setting. Approach and Results—: The CRIC Study (Chronic Renal Insufficiency Cohort) is an ongoing prospective study of 3939 participants with chronic kidney disease. In 3635 CRIC participants with genotype data, carriers of the rs10455872 or rs6930542 variants had a higher median Lp(a) level (mg/dL) compared with noncarriers (73 versus 23; P <0.001 and 56 versus 22; P <0.001, respectively). The 3744 participants (55% male and 41% non-Hispanic White) with available baseline Lp(a) levels were stratified into quartiles of baseline Lp(a) (mg/dL): <9.8, 9.8 to 26.0, 26.1 to 61.3, and >61.3. There were 315 myocardial infarctions and 822 deaths during a median follow-up of 7.5 years. The second quartile had the lowest event rate. After adjusting for potential confounders and using a Cox proportional hazards model, the highest quartile of Lp(a) was associated with increased risk of myocardial infarction (hazard ratio, 1.49; 95% confidence interval, 1.05–2.11), death (hazard ratio, 1.28; 95% confidence interval, 1.05–1.57), and the composite outcome (hazard ratio, 1.29; 95% confidence interval, 1.07–1.56) compared with the second quartile of Lp(a). Conclusions—: Among adults with chronic kidney disease, elevated Lp(a) is independently associated with myocardial infarction and death. Future studies exploring pharmacological Lp(a) reduction in this population are warranted. Abstract : Supplemental Digital Content is available in the text.